Selection analysis of road maintenance methods between the use of slurry seals and spot levelling from service life and construction costs aspects - Tri C. Utomo; Catur A. Prastyanto (Institut Teknologi Sepuluh Nopember (ITS), 2023)
On national roads with high or equal average daily traffic compared to provincial roads, slurry seals are commonly used to protect the asphalt layer from damage and improve skid resistance. Interestingly, when applied to provincial roads, spot leveling treatments tend to have a longer lifespan than slurry seals, which often deteriorate within the same fiscal year. This creates a contradiction: provincial roads with lower traffic tend to benefit more from spot leveling, while national roads, with higher traffic, favor slurry seals. To address this discrepancy, further research is needed to understand the factors influencing method selection and compare the longevity of these treatments to their construction costs. The study utilized average daily traffic data to assess traffic conditions, surveyed road conditions to determine damage percentages and remaining service life for slurry seals and spot leveling, and then compared these findings with construction expenses. The Cumulative Equivalent Single Axle (CESA) value, reflecting traffic load characteristics, significantly impacts the service life of slurry seals, resulting in a 2.08-year difference and a handling cost of Rp. 12,949.29 per square meter per year. Drainage conditions also affect slurry seal longevity, with a 1.32 year service life gap and handling cost of Rp. 8,097 per square meter per year. Additionally, sidewalk conditions influence slurry seal service life, leading to a 0.52-year gap and a handling cost of Rp. 4,688.39 per square meter per year. Based on the data regarding service life gaps and handling costs, it is evident that the most influential factor on the service life of slurry seals is the Cumulative Equivalent Single Axle (CESA) condition on the road segment where the slurry seal is applied.